Spatial variability of hypoxia and coupled physical-biogeochemical controls off the Changjiang (Yangtze River) Estuary in summer - Wei, Qinsheng; Yuan, Yongquan; Song, Shuqun; Zhao, Yuhang; Sun, Junchuan; Li, Caiwen; Wang, Baodong (Frontiers in Marine Science, 2022)
Global estuarine hypoxia is among the most acute environmental issues, yet the recognition of hypoxia variability remains patchy. The Changjiang (Yangtze River) Estuary (CE) is well known as one of the largest estuarine hypoxic systems. However, the mechanisms controlling the spatial variability and heterogeneity of summer hypoxia have been rarely examined in this region. Based on observational data in the summer of 2013, the essential linkages between physical-biogeochemical processes and spatial variability of hypoxia were revealed off the CE. The hypoxia generally occurred in a transitional region off the CE, presenting to be spatially variable and heterogeneous in its distribution and intensity. The river plume, stratification, front, upwelling and localized high phytoplankton biomass combine to shape the spatial morphology and scope of hypoxia. The spatial heterogeneity of hypoxic magnitude in horizontal direction is mainly regulated by the intensity variability of stratification and phytoplankton blooms. The position of bottom front formed by the offshore Taiwan Warm Current (TWC) and coastal water under tidal mixing controls the shoreward boundary of hypoxic zone, while the river plume front-dominated outer edge of phytoplankton blooms in upper layers plays a role in determining the seaward limit of the reach of bottom hypoxia. The stratification depth controlled by the upwelling and river plume governs the upper limit of the top reach of hypoxia, and shapes the vertical morphology of hypoxic zone. We contextualize the role of physical-biogeochemical drivers to the spatially variable hypoxia in a conceptual diagram. The findings would considerably contribute to our understanding of the spatially variable hypoxia in river plume-upwelling-front coupled estuarine systems, providing a sound basis for prediction and simulation under anticipated future conditions.